2015
DOI: 10.1016/j.jtumed.2015.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Daytime sleepiness and chronic sleep deprivation effects on academic performance among the Sudanese medical students

Abstract: Objectives:The literature has shown a negative impact of daytime sleepiness on the academic performance of medical students. This study explored the relationship between academic performance, sleep deprivation, and daytime sleepiness among Sudanese medical students.Methods: This cross-sectional study was conducted on 108 medical students from Omdurman University during the period from June to August 2014. Male and female students with excellent (A) and average (C) grades in the clinical phases of their studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
1
10

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 11 publications
2
14
1
10
Order By: Relevance
“…None A good proportion of students in this study reported going late to bed which is a common finding also reported in other studies (3,7,(21)(22).The interesting finding in the current study is related to sleep onset latency i.e. time taken to fall asleep after going to bed.…”
Section: Fundssupporting
confidence: 82%
“…None A good proportion of students in this study reported going late to bed which is a common finding also reported in other studies (3,7,(21)(22).The interesting finding in the current study is related to sleep onset latency i.e. time taken to fall asleep after going to bed.…”
Section: Fundssupporting
confidence: 82%
“…[11,13] In the study by Hyder O et al which evaluated the effects of chronic sleep deprivation and day time sleepiness in Sudanese medical students the tendency to doze was found to be highest while sitting and reading (88%) with obvious adverse consequences on their academic performance. [14] Circadian rhythm disorders in the form of delayed sleep phase syndrome marked by significant delays in sleep/wake cycles are common among college students and may result in increased daytime sleepiness. [15] Sleep deprivation is common in medical training and the high academic load and anxiety regarding examinations leading to use of central nervous system stimulants to delay sleep at night may be other causes of daytime sleepiness in medical students which hamper their academic performance.…”
Section: Discussionmentioning
confidence: 99%
“…Entre los hallazgos se estableció que al menos el 83,0 % de las personas que participaron de dicha investigación eran "malos dormidores" con disfunción leve del sueño, así como que al menos un 53,8 % dormía menos de 6 horas diarias en promedio (38,43). Puede indicarse que los resultados encontrados en la presente investigación en la que se incluyeron estudiantes de diferentes programas de pregrado, no solo del área de la salud, coinciden con lo señalado en otros estudios en los que se refiere que la privación crónica del sueño, la mala calidad del sueño y la presencia de la SDE, son comunes entre los estudiantes universitarios y de manera especial entre los estudiantes de medicina (48)(49)(50).…”
Section: Discussionunclassified
“…Los resultados reportados en la presente investigación, realizada con una muestra de estudiantes de diferentes carreras universitarias, que incluyó diferentes áreas de dominio y de formación en el marco de la educación superior, constituyen un hallazgo significativo en el contexto de los estudios de problemas del sueño en estudiantes universitarios; en cuanto a los resultados encontrados, estos permiten señalar que problemas como la SDE y la baja calidad del sueño parecen estar presentes no solo entre estudiantes y profesionales del área de la salud sino que parecen propios de la vida del estudiante universitario en diferentes áreas del saber científico en general (51-52); representando así un problema emergente de salud para el adulto joven. Los hallazgos encontrados en la presente investigación contribuyen a confirmar la tendencia descrita por otros investigadores que reconocen a la población joven como particularmente propensa a presentar problemas del sueño (48)(49)(50)(51)(52).…”
Section: Discussionunclassified